Institutions and Agricultural Productivity in Low and Middle-income African Countries - Uduma, Kelechi; Adeagbo, Olayinka Afolakemi; Sokunbi, Gbenro Mathew; Ajose, Olufemi Aina; Osabohien, Romanus (Acta Universitatis Danubius. Œconomica, 2023)
The study examines the impact of institutions on agricultural productivity across 45 countries in Africa. Panel data series for the 45 countries sought from World Bank Development Indicators (WDI), Food and Agricultural Organisation (FAO) and Country Policy and Institutional Assessment (CPIA) were used for the analysis. The other socioeconomic variables considered in this study are agricultural land, investment in agriculture, agricultural employment, and technology. The study estimated the pooled ordinary least squares, fixed effect model, random effect model and system generalised method of moments (GMM). The Hausman test was used to select between the fixed effect and random effect models. At a 5% significance level, the fixed effect model was preferred. Principal Component Analysis was used to generate institution index from six indicators of institutions engaged in the study. The result showed that institution has a significant positive impact on agricultural productivity. The study concluded that the quality of institutions is crucial for advancing agricultural productivity in these countries. It would prevent embezzlement and the existence of poor policies that halt agricultural productivity and the outflow of investment in the sector. In conclusion, in order to constantly promote agricultural productivity, the quality of institutions should be strengthened in these countries. Hence, ways to do so must be addressed by the relevant stakeholders. This includes increased checks and balances to have better control of corruption and improved index for voice and accountability. The study used a panel data and therefore, do not account for the effect of institutions at the country level.